Presentation is loading. Please wait.

Presentation is loading. Please wait.

Viscoelasticity and Wave Propagation

Similar presentations


Presentation on theme: "Viscoelasticity and Wave Propagation"β€” Presentation transcript:

1 Viscoelasticity and Wave Propagation
Part I Gaurav Dutta King Abdullah University of Science and Technology September 6, 2016

2 Outline Introduction to viscoelasticity
Stress-strain relationship and complex modulus Strain energy density Q Summary

3 Outline Introduction to viscoelasticity
Stress-strain relationship and complex modulus Strain energy density Q Summary

4 Viscoelasticity 𝜎(𝑑)= 𝑀 𝑒 πœ–(𝑑)
Viscoelasticity is the property of materials that exhibit both viscous and elastic characteristics when undergoing deformation 𝜎(𝑑)= 𝑀 𝑒 πœ–(𝑑) Stress Strain Purely elastic material Stress Strain Viscoelastic material Loading Loading Energy Loss Unloading Unloading Hysteresis plot

5 Stress-strain Relationship
Constant Strain Stress Relaxation 𝜎(𝑑)=πœ“(𝑑)βˆ— πœ•πœ–(𝑑) πœ•π‘‘ Stress relaxation function Observed decrease in stress in response to the same amount of strain

6 Stress-strain Relationship
Constant Stress Creep πœ–(𝑑)=πœ‰(𝑑)βˆ— πœ•πœŽ(𝑑) πœ•π‘‘ Creep function Observed increase in strain in response to the same amount of stress

7 Viscoelastic Materials

8 Viscoelastic Materials

9 Outline Introduction to viscoelasticity
Stress-strain relationship and complex modulus Strain energy density Q Summary

10 Complex Modulus for viscoelastic media
Stress-strain relationship 𝜎= Stress, πœ–= Strain πœ“(𝑑)= relaxation function 𝜎(𝑑)=πœ“(𝑑)βˆ— πœ•πœ–(𝑑) πœ•π‘‘ For a lossless media 𝐻 𝑑 = Heaviside function πœ“ 𝑑 = 𝑀 𝑒 𝐻(𝑑) Hooke’s law 𝜎=πœ“ 𝑑 βˆ— πœ•πœ– πœ•π‘‘ = πœ•πœ“ 𝑑 πœ•π‘‘ βˆ—πœ–= 𝑀 𝑒 𝛿 𝑑 βˆ—πœ–= 𝑀 𝑒 πœ– 𝑀 𝑒 = Elastic Modulus

11 Complex Modulus for viscoelastic media
Stress-strain relationship 𝜎= Stress, πœ–= Strain πœ“(𝑑)= relaxation function 𝜎 𝑑 =πœ“ 𝑑 βˆ— πœ•πœ– 𝑑 πœ•π‘‘ = πœ•πœ“ πœ•π‘‘ βˆ—πœ– 𝑑 = πœ• 𝑑 πœ“ 𝑑 βˆ—πœ–(𝑑) After Fourier transform 𝐹= Fourier transform operator 𝐹 𝜎 πœ” =𝑀 πœ” 𝐹[πœ–(πœ”)] 𝑀 πœ” =𝐹 πœ• 𝑑 πœ“ 𝑑 = βˆ’βˆž +∞ πœ• 𝑑 πœ“ 𝑑 exp βˆ’π‘–πœ”π‘‘ 𝑑𝑑 𝑀 πœ” = Complex modulus

12 Complex Modulus for viscoelastic media
For a Heaviside function 𝑓(𝑑) 𝑀 πœ” = βˆ’βˆž +∞ πœ• 𝑑 πœ“ 𝑑 exp βˆ’π‘–πœ”π‘‘ 𝑑𝑑 𝑓 𝑑 = 𝑓 𝑑 𝐻(𝑑) If πœ“(𝑑) is of Heaviside type πœ“(𝑑)= causal function πœ“ 𝑑 = πœ“ (𝑑) for 𝑑>0 πœ“= πœ“ 𝐻(𝑑) πœ• 𝑑 πœ“=𝛿 𝑑 πœ“ + πœ• 𝑑 πœ“ 𝐻(𝑑) 𝑀 πœ” = 𝑀 1 πœ” +𝑖 𝑀 2 (πœ”) 𝑀 πœ” =πœ“ ∞ +π‘–πœ” 0 ∞ πœ“ 𝑑 βˆ’πœ“(∞) exp βˆ’π‘–πœ”π‘‘ 𝑑𝑑

13 Complex Modulus for viscoelastic media
𝑀 πœ” =πœ“ ∞ +π‘–πœ” 0 ∞ πœ“ 𝑑 βˆ’πœ“(∞) exp βˆ’π‘–πœ”π‘‘ 𝑑𝑑 𝑀 πœ” = 𝑀 1 πœ” +𝑖 𝑀 2 (πœ”) Storage Modulus 𝑀 1 πœ” =πœ” 0 ∞ πœ“ 𝑑 sin πœ”π‘‘ 𝑑𝑑 Loss Modulus M 2 πœ” =πœ” 0 ∞ πœ“ 𝑑 βˆ’πœ“(∞) cos πœ”π‘‘ 𝑑𝑑

14 Outline Introduction to viscoelasticity
Stress-strain relationship and complex modulus Strain energy density Q Summary

15 Strain Energy Density Strain energy density:
Energy stored by a system per unit volume while undergoing deformation 𝐸= 1 2 π‘‰πœŽπœ–= 1 2 𝑉 𝑀 𝑒 πœ– 2 Strain energy: 𝑉= Volume 𝑀 𝑒 = Elastic modulus π‘ˆ= 𝐸 𝑉 = 1 2 πœŽπœ–= 1 2 𝑀 𝑒 πœ– 2 Strain energy density: π‘ˆ 𝑑 = 1 2 𝜎 𝑖𝑗 πœ– 𝑖𝑗 = 1 2 𝐢 π‘–π‘—π‘˜π‘™ πœ– 𝑖𝑗 πœ– π‘˜π‘™

16 Q For elastic media: π‘ˆ 𝑑 = 1 2 𝜎 𝑖𝑗 πœ– 𝑖𝑗 = 1 2 𝐢 π‘–π‘—π‘˜π‘™ πœ– 𝑖𝑗 πœ– π‘˜π‘™
π‘ˆ 𝑑 = 1 2 𝜎 𝑖𝑗 πœ– 𝑖𝑗 = 1 2 𝐢 π‘–π‘—π‘˜π‘™ πœ– 𝑖𝑗 πœ– π‘˜π‘™ Loss Modulus Q β‡’ quantifies dissipation β‡’ π‘ π‘‘π‘Ÿπ‘Žπ‘–π‘› π‘’π‘›π‘’π‘Ÿπ‘”π‘¦ π‘ π‘‘π‘œπ‘Ÿπ‘’π‘‘ 𝑖𝑛 π‘‘β„Žπ‘’ π‘£π‘œπ‘™π‘’π‘šπ‘’ π‘’π‘›π‘’π‘Ÿπ‘”π‘¦ π‘™π‘œπ‘ π‘‘ 𝑖𝑛 π‘’π‘Žπ‘β„Ž 𝑐𝑦𝑐𝑙𝑒 = 𝐸 Δ𝐸 𝑀 πœ” = 𝑀 1 πœ” +𝑖 𝑀 2 (πœ”) Storage Modulus π‘ˆ= 𝐸 𝑉 = 1 2 πœŽπœ–= 1 2 𝑀 𝑒 πœ– 2 Strain energy density: Energy stored in the volume: 𝐸= 1 2 𝑀 1 πœ– 2 𝑄= 𝐸 Δ𝐸 = 𝑀 1 πœ– 𝑀 2 πœ– 2 = π‘…π‘’π‘Žπ‘™ (𝑀(πœ”)) πΌπ‘š(𝑀(πœ”)) Energy lost:Δ𝐸= 1 2 𝑀 2 πœ– 2

17 Strain Energy Density For elastic media:
π‘ˆ 𝑑 = 1 2 𝜎 𝑖𝑗 πœ– 𝑖𝑗 = 1 2 𝐢 π‘–π‘—π‘˜π‘™ πœ– 𝑖𝑗 πœ– π‘˜π‘™ For viscoelastic media: 𝜎(𝑑)=πœ“(𝑑)βˆ— πœ•πœ–(𝑑) πœ•π‘‘ 𝐢 π‘–π‘—π‘˜π‘™ β‡’πœ“( 𝜏 1 + 𝜏 2 ) πœ– 𝑖𝑗 β‡’ πœ• 𝜏 1 πœ–(π‘‘βˆ’ 𝜏 1 ) πœ– π‘˜π‘™ β‡’ πœ• 𝜏 2 πœ–(π‘‘βˆ’ 𝜏 2 ) π‘ˆ 𝑑 = ∞ 0 ∞ πœ“ 𝜏 1 + 𝜏 2 πœ•πœ– π‘‘βˆ’ 𝜏 1 πœ•πœ– π‘‘βˆ’ 𝜏 2 𝑑 𝜏 1 𝑑 𝜏 2

18 Strain Energy Density Strain energy density:
π‘ˆ 𝑑 = ∞ 0 ∞ πœ“ 𝜏 1 + 𝜏 2 πœ• 𝜏 1 πœ– π‘‘βˆ’ 𝜏 1 πœ• 𝜏 2 πœ– π‘‘βˆ’ 𝜏 2 𝑑 𝜏 1 𝑑 𝜏 2 1) Take the time-average over a period 2πœ‹/πœ” 2) Use the relation: <𝑅𝑒 𝒂 𝑇 ⋅𝑅𝑒 𝒃 > = 1 2 𝑅𝑒( 𝒂 𝑇 β‹… 𝒃 βˆ— ) Time-averaged strain energy density: <π‘ˆ 𝑑 > = πœ– 2 𝑀 1 𝑀 πœ” = 𝑀 1 πœ” +𝑖 𝑀 2 (πœ”) Time-averaged rate of dissipated strain energy density: < 𝑉 𝑑 > = πœ” πœ– 2 𝑀 2

19 Outline Introduction to viscoelasticity
Stress-strain relationship and complex modulus Strain energy density Q Summary

20 Definition of Q 𝑄 = Quality factor 𝑄 βˆ’1 = Dissipation factor
Time-averaged strain energy density: <π‘ˆ 𝑑 > = πœ– 2 𝑀 1 Time-averaged rate of dissipated strain energy density: < 𝑉 𝑑 > = πœ” πœ– 2 𝑀 2 Define time-averaged dissipated strain energy density: <𝑉 𝑑 > = πœ” βˆ’1 < 𝑉(𝑑) > Q β‡’ quantifies dissipation β‡’ 2βˆ— π‘‘π‘–π‘šπ‘’βˆ’π‘Žπ‘£π‘” π‘ π‘‘π‘Ÿπ‘Žπ‘–π‘› π‘’π‘›π‘’π‘Ÿπ‘”π‘¦ 𝑑𝑒𝑛𝑠𝑖𝑑𝑦 π‘‘π‘–π‘šπ‘’βˆ’π‘Žπ‘£π‘” π‘‘π‘–π‘ π‘ π‘–π‘π‘Žπ‘‘π‘’π‘‘ π‘’π‘›π‘’π‘Ÿπ‘”π‘¦ 𝑑𝑒𝑛𝑠𝑖𝑑𝑦 𝑄= 2Γ—π‘ˆ(𝑑) 𝑉(𝑑) = 2Γ— πœ– 2 𝑀 πœ– 2 𝑀 2 = 𝑀 1 𝑀 2 𝑀 πœ” = 𝑀 1 πœ” +𝑖 𝑀 2 (πœ”) 𝑄 = Quality factor 𝑄= 𝑅𝑒(𝑀) πΌπ‘š(𝑀) 𝑀 1 πœ” , 𝑀 2 (πœ”) β‰₯0 𝑄 βˆ’1 = Dissipation factor

21 Outline Introduction to viscoelasticity
Stress-strain relationship and complex modulus Strain energy density Q Summary

22 Properties of the relaxation function
1) πœ“ 𝑑 = πœ“ 𝑑 𝐻(𝑑) πœ“ 𝑑 = causal function 2) Strain energy density: π‘ˆ 𝑑 = 1 2 𝜎 𝑖𝑗 πœ– 𝑖𝑗 = 1 2 𝐢 π‘–π‘—π‘˜π‘™ πœ– 𝑖𝑗 πœ– π‘˜π‘™ Elastic π‘ˆ 𝑑 = 1 2 πœ“ π‘–π‘—π‘˜π‘™ (𝑑) πœ– 𝑖𝑗 πœ– π‘˜π‘™ Viscoelastic π‘ˆ 𝑑 β‰₯0 πœ“ π‘–π‘—π‘˜π‘™ 𝑑 β‰₯0 πœ“= πœ“ 𝐻(𝑑) πœ“ 𝑑 = positive real function

23 Properties of the relaxation function
3) Fading memory hypothesis: The value of the stress depends more strongly upon the recent history than upon the remote history of the strain. πœ“ 𝑑 = decreasing function of time πœ•πœ“ πœ•π‘‘ t= t 1 ≀ πœ•πœ“ πœ•π‘‘ t= 𝑑 2 , 𝑑 1 > 𝑑 2 >0

24 Mechanical models and viscoelasticity
Part II Gaurav Dutta King Abdullah University of Science and Technology September 7, 2016

25 Mechanical models and wave propagation
For elastic medium: Spring 𝜎= 𝑀 𝑒 πœ– For viscoelastic medium: 𝜎= πœ• 𝑑 πœ“βˆ—πœ– Dashpot (dissipates energy) Spring (stores energy) +

26 Mechanical models and wave propagation
Maxwell Model Kelvin-Voigt Model Zener or SLS Model

27 Maxwell Model 𝜎= 𝑀 π‘ˆ πœ– 1 πœ• 𝑑 = πœ• πœ•π‘‘ 𝜎=πœ‚ πœ• 𝑑 πœ– 2 πœ–= πœ– 1 + πœ– 2 𝜎=π‘€πœ–
𝜎= 𝑀 π‘ˆ πœ– 1 Spring πœ• 𝑑 = πœ• πœ•π‘‘ 𝜎=πœ‚ πœ• 𝑑 πœ– 2 Dashpot πœ–= πœ– 1 + πœ– 2 𝑀 π‘ˆ = elastic const. of spring πœ‚= viscosity πœ• 𝑑 𝜎 𝑀 π‘ˆ + 𝜎 πœ‚ = πœ• 𝑑 πœ– 𝜎=π‘€πœ– 𝜏= πœ‚ 𝑀 π‘ˆ 𝑀 πœ” = πœ”πœ‚ πœ”πœβˆ’π‘– 𝐹 𝜎 πœ” =𝑀 πœ” 𝐹[πœ–(πœ”)] Relaxation time Complex Modulus

28 Relaxation function for Maxwell model
𝜏= πœ‚ 𝑀 π‘ˆ 𝑀 πœ” = πœ”πœ‚ πœ”πœβˆ’π‘– πœ–(𝑑)=𝐻(𝑑) Measure the stress after applying a constant unit strain 𝜎 𝑑 = πœ• 𝑑 πœ“ 𝑑 βˆ—πœ– 𝑑 =πœ“ 𝑑 βˆ— πœ• 𝑑 πœ– 𝑑 =πœ“ 𝑑 βˆ—π›Ώ 𝑑 =πœ“(𝑑) πœ• 𝑑 𝜎 𝑀 π‘ˆ + 𝜎 πœ‚ = πœ• 𝑑 πœ– πœ•πœ“ πœ•π‘‘ + πœ“ 𝜏 = 𝑀 π‘ˆ 𝛿 𝑑 β‡’πœ“ 𝑑 = 𝑀 π‘ˆ exp βˆ’π‘‘/𝜏 𝐻(𝑑) Relaxation function

29 Creep function and Q for Maxwell model
Measure the strain after applying a constant unit stress 𝜎(𝑑)=𝐻(𝑑) πœ– 𝑑 =πœ‰ 𝑑 βˆ— πœ• 𝑑 𝜎 𝑑 =πœ‰ 𝑑 βˆ—π›Ώ 𝑑 =πœ‰(𝑑) πœ• 𝑑 𝜎 𝑀 π‘ˆ + 𝜎 πœ‚ = πœ• 𝑑 πœ–β‡’πœ‰ 𝑑 = 1 𝑀 π‘ˆ 1+ 𝑑 𝜏 𝐻(𝑑) Creep function Q: 𝑄= 𝑅𝑒(𝑀(πœ”)) πΌπ‘š(𝑀(πœ”)) = 𝑀 1 𝑀 2 =πœ”πœ 𝑀 πœ” = πœ”πœ‚ πœ”πœβˆ’π‘– = 𝑀 1 +𝑖 𝑀 2 𝜏= πœ‚ 𝑀 π‘ˆ

30 Relaxation/Creep function for Maxwell model
πœ‰ 𝑑 = 1 𝑀 π‘ˆ 1+ 𝑑 𝜏 𝐻(𝑑) πœ“ 𝑑 = 𝑀 π‘ˆ exp βˆ’π‘‘/𝜏 𝐻(𝑑) 𝜏= πœ‚ 𝑀 π‘ˆ 1) Creep function resembles the creep function of a viscous fluid. 2) There is no asymptotical residual stress as seen in real solids !!!

31 Kelvin-Voigt Model 𝜎= 𝜎 1 + 𝜎 2 = 𝑀 𝑅 πœ–+πœ‚ πœ• 𝑑 πœ– Relaxation function:
πœ“ 𝑑 = 𝑀 𝑅 𝐻 𝑑 +πœ‚π›Ώ(𝑑) Creep function: Complex Modulus: 𝑀 πœ” = 𝑀 𝑅 +π‘–πœ”πœ‚ πœ– πœ‰ 𝑑 = 1 𝑀 𝑅 1βˆ’ exp βˆ’ 𝑑 𝜏 𝐻(𝑑) Relaxation time: 𝜏= πœ‚ 𝑀 𝑅 𝑄 πœ” = π‘…π‘’π‘Žπ‘™ 𝑀 πœ” πΌπ‘šπ‘Žπ‘”(𝑀(πœ”)) = 1 πœ”πœ

32 Relaxation/Creep function for KV model
πœ‰ 𝑑 = 1 𝑀 𝑅 1βˆ’ exp βˆ’ 𝑑 𝜏 𝐻(𝑑) πœ“ 𝑑 = 𝑀 𝑅 𝐻 𝑑 +πœ‚π›Ώ(𝑑) 𝜏= πœ‚ 𝑀 𝑅 Relaxation function has no time dependence. Creep function lacks the instantaneous response of real solids !!!

33 Experimental Creep function for solids

34 Standard Linear Solid Model
Zener or SLS Model 𝜎= π‘˜ 1 πœ– 1 𝜎 1 =πœ‚ πœ• 𝑑 πœ– 2 𝜎 2 = π‘˜ 2 πœ– 2 𝜎= 𝜎 1 + 𝜎 2 πœ–= πœ– 1 + πœ– 2 Stress-strain relationship: 𝜎+ 𝜏 𝜎 πœ•πœŽ πœ•π‘‘ = 𝑀 𝑅 (πœ–+ 𝜏 πœ– πœ•πœ– πœ•π‘‘ ) 𝑀 𝑅 = π‘˜ 1 π‘˜ 2 π‘˜ 1 + π‘˜ 2 𝜏 𝜎 = πœ‚ π‘˜ 1 + π‘˜ 2 𝜏 πœ– = πœ‚ π‘˜ 2 Strain relaxation time Relaxed Modulus Stress relaxation time

35 Standard Linear Solid Model
Zener or SLS Model Stress-strain relationship: 𝜎+ 𝜏 𝜎 πœ•πœŽ πœ•π‘‘ = 𝑀 𝑅 (πœ–+ 𝜏 πœ– πœ•πœ– πœ•π‘‘ ) After taking Fourier transform on both sides 𝑀 πœ” = 𝑀 𝑅 1+π‘–πœ” 𝜏 πœ– 1+π‘–πœ” 𝜏 𝜎 𝜏 𝜎 = πœ‚ π‘˜ 1 + π‘˜ 2 𝑀 𝑅 = π‘˜ 1 π‘˜ 2 π‘˜ 1 + π‘˜ 2 𝜏 πœ– = πœ‚ π‘˜ 2 πœ–(𝑑)=𝐻(𝑑) πœ“ 𝑑 = 𝑀 𝑅 1βˆ’ 1βˆ’ 𝜏 πœ– 𝜏 𝜎 exp βˆ’ 𝑑 𝜏 𝜎 𝐻(𝑑) Relaxation function: πœ‰ 𝑑 = 1 𝑀 𝑅 1βˆ’ 1βˆ’ 𝜏 𝜎 𝜏 πœ– exp βˆ’ 𝑑 𝜏 πœ– 𝐻(𝑑) Creep function: 𝜎(𝑑)=𝐻(𝑑)

36 Relaxation/Creep function for SLS model
πœ‰ 𝑑 = 1 𝑀 𝑅 1βˆ’ 1βˆ’ 𝜏 𝜎 𝜏 πœ– exp βˆ’ 𝑑 𝜏 πœ– 𝐻(𝑑) πœ“ 𝑑 = 𝑀 𝑅 1βˆ’ 1βˆ’ 𝜏 πœ– 𝜏 𝜎 exp βˆ’ 𝑑 𝜏 𝜎 𝐻(𝑑) 𝜏 𝜎 = πœ‚ π‘˜ 1 + π‘˜ 2 𝜏 πœ– = πœ‚ π‘˜ 2

37 Experimental Creep function for solids

38 Q for SLS model 𝑀 πœ” = 𝑀 𝑅 1+π‘–πœ” 𝜏 πœ– 1+π‘–πœ” 𝜏 𝜎 = 𝑀 1 +𝑖 𝑀 2 𝑣 πœ” = 𝑀 πœ” 𝜌 𝑄(πœ”)= 𝑅𝑒(𝑀(πœ”)) πΌπ‘š(𝑀(πœ”)) = 𝑀 1 𝑀 2 = 1+ πœ” 2 𝜏 πœ– 𝜏 𝜎 πœ”( 𝜏 πœ– βˆ’ 𝜏 𝜎 ) 𝑑𝑄 πœ” π‘‘πœ” =0 πœ” 0 = 1 𝜏 0 = 𝜏 πœ– 𝜏 𝜎

39 Q for SLS model 𝑄(πœ”)= 1+ πœ” 2 𝜏 πœ– 𝜏 𝜎 πœ”( 𝜏 πœ– βˆ’ 𝜏 𝜎 )
𝑄(πœ”)= 1+ πœ” 2 𝜏 πœ– 𝜏 𝜎 πœ”( 𝜏 πœ– βˆ’ 𝜏 𝜎 ) πœ” 0 = 1 𝜏 = 𝜏 πœ– 𝜏 𝜎 ⇒𝑄 0 = 2 𝜏 0 𝜏 πœ– βˆ’ 𝜏 𝜎 𝜏 πœ– = 𝜏 0 𝑄 𝑄 𝜏 𝜎 = 𝜏 0 𝑄 𝑄 βˆ’1

40 Generalized SLS model Stress-strain relationship: Total stress:
𝜎 𝑙 + 𝜏 πœŽπ‘™ πœ• 𝜎 𝑙 πœ•π‘‘ = 𝑀 𝑅𝑙 (πœ–+ 𝜏 πœ–π‘™ πœ•πœ– πœ•π‘‘ ) 𝑙 =1,…,L 𝑀 𝑙 πœ” = 𝑀 𝑅𝑙 1+π‘–πœ” 𝜏 πœ–π‘™ 1+π‘–πœ” 𝜏 πœŽπ‘™ 𝑀 𝑅𝑙 = π‘˜ 1𝑙 π‘˜ 2𝑙 π‘˜ 1𝑙 + π‘˜ 2𝑙 𝜏 πœŽπ‘™ = πœ‚ 𝑙 π‘˜ 1𝑙 + π‘˜ 2𝑙 Total stress: 𝜎= 𝑙=1 𝐿 𝜎 𝑙 𝜏 πœ–π‘™ = πœ‚ 𝑙 π‘˜ 2𝑙

41 Generalized SLS model Total stress: 𝑀 𝑅 = 𝐿𝑀 𝑅𝑙 Relaxation function:
𝜎= 𝑙=1 𝐿 𝜎 𝑙 = 𝑙=1 𝐿 𝑀 𝑙 πœ– = 𝑙=1 𝐿 𝑀 𝑅𝑙 1+π‘–πœ” 𝜏 πœ–π‘™ 1+π‘–πœ” 𝜏 πœŽπ‘™ πœ– Relaxation function: πœ“ 𝑑 = 𝑀 𝑅 1βˆ’ 1 𝐿 𝑙=1 𝐿 1βˆ’ 𝜏 πœ–π‘™ 𝜏 πœŽπ‘™ exp βˆ’ 𝑑 𝜏 πœŽπ‘™ 𝐻(𝑑) 𝑀 𝑙 πœ” = 𝑀 𝑅𝑙 1+π‘–πœ” 𝜏 πœ–π‘™ 1+π‘–πœ” 𝜏 πœŽπ‘™ 𝜏 πœ–π‘™ = πœ‚ 𝑙 π‘˜ 2𝑙 𝜏 πœŽπ‘™ = πœ‚ 𝑙 π‘˜ 1𝑙 + π‘˜ 2𝑙 𝑀 𝑅 = 𝐿𝑀 𝑅𝑙

42 Viscoacoustic wave-equation
Zener or SLS Model πœ“ 𝑑 =𝐾 1βˆ’ 1βˆ’ 𝜏 πœ– 𝜏 𝜎 exp βˆ’ 𝑑 𝜏 𝜎 𝐻(𝑑) 𝜎= πœ• 𝑑 πœ“βˆ—πœ– βˆ’ 𝑝 =𝐾 1βˆ’ 1βˆ’ 𝜏 πœ– 𝜏 𝜎 𝑣 π‘₯ + 𝐾 𝜏 𝜎 1βˆ’ 𝜏 πœ– 𝜏 𝜎 exp βˆ’ 𝑑 𝜏 𝜎 𝐻 𝑑 βˆ— 𝑣 π‘₯ 𝜎=βˆ’π‘ πœ•π‘£ πœ•π‘₯ =𝑣 π‘₯ = πœ– π‘Ÿ (memory variable)

43 Viscoacoustic wave-equation
Zener or SLS Model π‘Ÿ= 𝐾 𝜏 𝜎 1βˆ’ 𝜏 πœ– 𝜏 𝜎 exp βˆ’ 𝑑 𝜏 𝜎 𝐻 𝑑 βˆ— 𝑣 π‘₯ πœ•π‘Ÿ πœ•π‘‘ =βˆ’ π‘Ÿ 𝜏 𝜎 + 𝐾 𝜏 𝜎 1βˆ’ 𝜏 πœ– 𝜏 𝜎 𝑣 π‘₯ Viscoacoustic wave-equations βˆ’ πœ•π‘ πœ•π‘‘ =𝐾 1βˆ’ 1βˆ’ 𝜏 πœ– 𝜏 𝜎 𝑣 π‘₯ +π‘Ÿ Newton’s law: βˆ’ 1 𝜌 πœ•π‘ πœ•π‘₯ = πœ• 𝑣 π‘₯ πœ•π‘‘

44 Viscoacoustic wave-equation
πœ• π‘Ÿ 𝑙 πœ•π‘‘ =βˆ’ π‘Ÿ 𝑙 𝜏 πœŽπ‘™ + 𝐾 𝜏 πœŽπ‘™ 1βˆ’ 𝜏 πœ–π‘™ 𝜏 πœŽπ‘™ 𝑣 π‘₯ Generalized SLS Model 𝑙 =1,…,L βˆ’ πœ•π‘ πœ•π‘‘ =𝐾 1βˆ’ 1 𝐿 𝑙=1 𝐿 1βˆ’ 𝜏 πœ–π‘™ 𝜏 πœŽπ‘™ 𝑣 π‘₯ + 1 𝐿 𝑙=1 𝐿 π‘Ÿ 𝑙 βˆ’ 1 𝜌 πœ•π‘ πœ•π‘₯ = πœ• 𝑣 π‘₯ πœ•π‘‘


Download ppt "Viscoelasticity and Wave Propagation"

Similar presentations


Ads by Google